Stability indicating HPLC-Fluorescence detection method for the simultaneous determination of linagliptin and empagliflozin in their combined pharmaceutical preparation - Rizk, Mohamed; Attia, Ali Kamal; Mohamed, Heba Yosry; Elshahed, Mona (European Journal of Chemistry, 2021)
A sensitive, accurate, and precise liquid chromatographic method has been developed and validated for the determination of Linagliptin (LNG) and Empagliflozin (EMP) in their combined tablets. Chromatographic separation was carried out on ODS-3 Inertsil® C18 column (150×4.6 mm, 5 µm). The mobile phase A (consisting of 0.30% Triethyl amine buffer (TEA) at pH = 4.5, adjusted using ortho-phosphoric acid); the mobile phase B (consisting of acetonitrile) was pumped through the column whose temperature was maintained at 40 °C, with a flow rate 1.7 mL/min, using gradient elution from 0-3 min A:B (75:25, v:v), then from 3-6 min the ratio changed to be A:B (60:40, v:v). Fluorescence detection (FLD) was performed at 410 nm after excitation at 239 nm. Acceptable linearity, accuracy and precision values of the proposed method were found over the concentration ranges of 0.5-15 µg/mL for LNG and 1.0-30 µg/mL for EMP with correlation coefficients of 0.9997 and 0.9998 in the case of LNG and EMP, respectively. The recoveries and relative standard deviations percentages were found in the following ranges: 98.56-101.85 and 0.53-1.52% for LNG and 98.00-101.95 and 0.31-1.05% for EMP. The detection and quantification limits were 0.15 and 0.45 µg/mL for LNG and 0.22 and 0.67 µg/mL for EMP. The optimized method was validated and proved to be specific, robust, accurate and reliable for the determination of the drugs in pure form or in their combined pharmaceutical preparations. No significant difference was found regarding accuracy and precision upon statistical comparison between the obtained results of the proposed method and those of the reported method. Furthermore, the proposed method is proved to be a stability-indicating assay after exposure of the studied drugs to variable forced degradation parameters, such as acidic, alkaline and oxidative conditions, according to the recommendations of the International Conference on Harmonization guidelines. The simplicity and selectivity of the proposed method allows its use in quality control laboratories.